JUAL BELI ‘INAH SEBAGAI SOLUSI TRANSAKSI BEBAS RIBA PERSPEKTIF HUKUM ISLAM - Ainun Barakah; Pipin Suitra; Ulfatun Najiha (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2020)
Buying and selling is an economic transaction that cannot be separated from everyday human life. As social beings, humans need interaction with one another, including in fulfilling their daily needs. Buying and selling in Islam is not only seen as a medium of transactions between sellers and buyers who are not bound by rules. In Islam, every muamalah transaction that occurs between an individual and another or a group and community must be built on the principle of mutual benefit, and must avoid the existence of aggrieved parties, then the transaction must also be separated from the usury system. In fact, because of a pressing need, tactics are often carried out to avoid usury, especially qardh (debt) which is common and widespread among the people, among these tactics is to implement the 'inah contract. What is the description and law of the 'inah' contract, then what is the hilah law in this case, these two things will be discussed by comparing the opinions of the jurists along with the arguments of each party. To get and know about the law of 'inah' contract, the author uses the library research method. The research results show that the 'inah buying and selling contract as a solution to riba-free transactions is debated by the law among the jurists, some allow it with one note, but jumhur fuqaha is forbidden for several reasons.